LIMIT FACTORS AND THE PATHOLOGY OF ANIMALS OF ANTENATAL AND POSTNATAL DEVELOPMENT - Цвіліховський, М. І.; Береза, В. І.; Немова, Т. В.; Якимчук, О. М. (Scientific Progress & Innovations, 2014)
Shows the interaction of limit factors and their role in the occurrence of pathologies in antenatal and postnatal periods of animals. Established that the level of environmental factors that are beyond the minimum or maximum values leading to different types disorders in animal organism. Environmental factors influence on animals not separately but comprehensively in different ratios. Established that antenatal pathology of animals is a negative effect of "non-environmental activity" of people in livestock.